Embryological Exegesis in Classical and Modern Qur’anic Interpretation: Al-Kasysyāf and Al-Jawāhir - Adi Sunarya; M. Ridwan Hasbi; Masyhuri Putra (Jurnal Intelek Insan Cendikia, 2024)
This study examines the methodological frameworks employed in interpreting Qur’anic embryological verses through a comparative analysis of Az-Zamakhsyari’s Al-Kasysyāf and Tantawi Jawhari’s Al-Jawāhir. Using a systematic comparative-analytical approach, this research investigates their distinctive interpretative methods concerning human embryological development (Q.S. Al-Mu’minun 23:12-14; As-Sajdah 32:7-9; Al-Insan 76:2). The study reveals how Az-Zamakhsyari’s linguistic-rational methodology and Jawhari’s empirical-scientific approach offer complementary insight into Qur’anic embryological discourse. This research contributes to the contemporary discussion on the integration of scientific knowledge in Qur’anic exegesis while highlighting the historical development of tafsir ‘ilmi methodology